2019
DOI: 10.1038/s41375-018-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional cooperativity of p97 and histone deacetylase 6 in mediating DNA repair in mantle cell lymphoma cells

Abstract: p97 is an ATPase that works in concert with histone deacetylase 6 (HDAC6), to facilitate the degradation of misfolded proteins by autophagosomes. p97 has also been implicated in DNA repair and maintaining genomic stability. In this study we determined the effect of combined inhibition of p97 and HDAC6 activities in mantle cell lymphoma (MCL) cells. We report that treatment with p97 inhibitors induces dose-dependent apoptosis in MCL cells. The p97 inhibitor CB-5083 induces ER stress markers GRP78 and CHOP and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The resistance of lung cancer cells to DDP is a complex process, involving multiple factors and genes, including the mechanisms of the accumulation and deactivation of intracellular drugs, DNA damage repair, autophagy, and apoptosis. [14][15][16][17] Recently more and more research has focused on the mechanism of Delicaflavone in tumors. It exerts antitumor activity by inducing apoptosis and autophagy and Figure 2 Delicaflavone united with DDP regulated lung cancer DDP resistant cells invasion, migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance of lung cancer cells to DDP is a complex process, involving multiple factors and genes, including the mechanisms of the accumulation and deactivation of intracellular drugs, DNA damage repair, autophagy, and apoptosis. [14][15][16][17] Recently more and more research has focused on the mechanism of Delicaflavone in tumors. It exerts antitumor activity by inducing apoptosis and autophagy and Figure 2 Delicaflavone united with DDP regulated lung cancer DDP resistant cells invasion, migration.…”
Section: Discussionmentioning
confidence: 99%
“…5×10 3 /well A549, A549/DDP, PC9, and PC9/DDP cells were inoculated into 96 well plates for 12 h, then, the different concentrations of delicaflavone (5,10,20,40 and 80 µM) or DDP (2,4,8,16 and 32 µM) were added. In the meantime, A549/DDP cells were cultured with delicaflavone (20 µM) or DDP (16 µM) or delicaflavone (20 µM)+DDP (16 µM).…”
Section: Cck8 Analysismentioning
confidence: 99%
“…In Staphylococcus aureus infection, GEF-H1 activity was blocked by HDAC6 down-regulation, and HDAC6 knockout and inhibition diminished ROCK-induced vascular leakage and inflammation (39). As a selective inhibitor of HDAC6, Ricolinostat has been proven to be of value attenuating oxidative stress to diminish inflammation and inducing apoptosis to inhibit tumor growth through various signaling pathways (40)(41)(42)(43). However, in this study Ricolinostat failed to prevent Ang II induced myofibroblast differentiation (a process accompanied by fibroblasts proliferation) and was discovered to promote GEF-H1 phosphorylation on Ser886 with enhanced activity of RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical treatment of MCL is prone to drug resistance. It has recently been shown that combined treatment with ricolinostat and the P97 inhibitor CB-5083 leads to accumulation of ubiquitinated protein aggregates, ER stress ( Figure 1C), and increases DNA damage, ultimately resulting in apoptosis (Vekaria et al, 2019). In addition, the interaction between MCL or other NHL cells and their microenvironment confers tumor cell drug resistance and clonogenicity.…”
Section: B Cell Non-hodgkin Lymphoma (B-nhl)mentioning
confidence: 99%
“…MCL originates from naive B cells ( Figure 1A ) and is characterized by dysregulation of cyclin D1 and DNA damage response pathways ( Nogai et al., 2011 ). p53 and cyclin D1 mutations and activation of the PI3K or NF-κB pathway lead to recurrence ( Vekaria et al., 2019 ). The current clinical treatment of MCL is prone to drug resistance.…”
Section: B Cell Non-hodgkin Lymphoma (B-nhl)mentioning
confidence: 99%